1985
DOI: 10.1149/1.2113961
|View full text |Cite
|
Sign up to set email alerts
|

The Electrorefinement of Indium Through an Aluminum Alkyl Complex Electrolyte

Abstract: High purity indium metal has been prepared by electrolysis at constant potential from a mixed normalAl+normalIn complex electrolyte that contains typically 2 normalmol Alfalse(C2H5)3 and 0.06 normalmol Infalse(C2H5)3 normalper mol C6H5CH2Nfalse(CH3)3F . Based on the results of cyclic voltammetry applied to the pure Al complex electrolyte and to the mixed electrolyte, a mechanism for the cathodic and anodic steps in the electrorefinement process is proposed. This mechanism is described by the following net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…It was concluded that, within the framework of the experimental errors, this is also valid for a solid solution of the type (Hgl_~Cd~)yTel_y(s). The quantitative analysis in [77] shows that the solid solution of HgTe and CdTe is almost ideal. Therefore, it can be supposed that in this solid solution the components are mixed as quasiregular solutions; that is, (18) where W and V are interaction constants that should be determined from the experimental data.…”
Section: The Te-vapour Pressure For Solid Hgl_xcd×te and Liquid Hgl_rmentioning
confidence: 99%
See 3 more Smart Citations
“…It was concluded that, within the framework of the experimental errors, this is also valid for a solid solution of the type (Hgl_~Cd~)yTel_y(s). The quantitative analysis in [77] shows that the solid solution of HgTe and CdTe is almost ideal. Therefore, it can be supposed that in this solid solution the components are mixed as quasiregular solutions; that is, (18) where W and V are interaction constants that should be determined from the experimental data.…”
Section: The Te-vapour Pressure For Solid Hgl_xcd×te and Liquid Hgl_rmentioning
confidence: 99%
“…Assume that Cd and Tea are ideal in the gas phase, and that the chemical potential of the mercury in the gas phase can be expressed in the terms of the fugacity of pttg, from [77], as…”
Section: The Te-vapour Pressure For Solid Hgl_xcd×te and Liquid Hgl_rmentioning
confidence: 99%
See 2 more Smart Citations
“…The methods for preparing high purity indium include ion exchange, zone melting, low halide, vacuum distillation and electrolytic refining, etc. [2][3][4][5][6][7][8][9][10] It is difficult to prepare high purity indium only by electrolysis unless several combinations of purification methods are applied. Electrorefining is a usual purification method, which can be easily scaled up.…”
Section: Introductionmentioning
confidence: 99%